PD-1 inhibition for relapse after allogeneic transplantation in acute myeloid leukemia and myelodysplastic syndrome - John M. Magenau; David G. Frame; Mary Riwes; John Maciejewski; Sarah Anand; Attaphol Pawarode; Anamarija M. Perry; Marcus Geer; Thomas Braun; Monalisa Ghosh; Pavan Reddy (Blood Advances)
Abstract: Relapse of acute myeloid leukemia (AML) and myelodysplastic syndrome (MDS) remains the primary source of mortality after allogeneic hematopoietic stem cell transplantation (HCT). Targeting programmed death-1 (PD-1) for reversing T-cell exhaustion and restoring the graft-versus-leukemia (GVL) effect may have logistical advantages over donor lymphocyte infusion. In a prospective phase 1B clinical trial, pembrolizumab was administered every 3 weeks to 16 patients with AML (n = 12) and MDS (n = 4) in relapse after HCT to assess graft-versus-host disease (GVHD), clinical response, and survival. The median time to relapse after HCT was 5.5 months and the median pretreatment bone marrow blast percentage was 21.5%. The overall response rate was 31.3% for patients receiving pembrolizumab, consisting of 3 complete remissions (18.8%) and 2 partial remissions (13.5%). The median duration of response was 610 days. A significantly greater proportion of patients with mixed CD3 chimerism had a clinical response than those with full donor chimerism (50% vs 0%; P = .03). Immune toxicities were frequent, with 37.5% of patients developing severe (grade 3-4) GVHD after pembrolizumab, of which most had resistance to corticosteroids and contributed to death in 4 patients (25%). The 1-year overall survival (OS) was 37.5% and event-free survival was 31.3%. For AML, 1-year OS was 50.0%. In this trial, PD-1 inhibition led to durable remission in one-third of the patients experiencing early relapse after HCT, suggesting that this approach may augment the GVL response. Responses were exclusively observed in the setting of mixed CD3 donor chimerism. Immune toxicities (GVHD) were a barrier to successful treatment outcome. This trial was registered at www.ClinicalTrials.gov as #NCT03286114.